Vowel prosthesis in Romance a diachronic study - Sampson, Rodney, 1944- (Oxford : Oxford University Press, 2010)
This text presents a comparative, historical account of vowel prosthesis in the Romance languages. The author describes in detail the formal characteristics, historical trajectory, and likely causes of the different types of prosthesis operating in Romance.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Romance languages -- Vowels; Romance languages -- History